Comparative Analysis of the Performance of Tchaikovsky’s Violin Concerto in D Major Opus 35 on Prima Kobyz and Violin (Música Hodie, 2025)
The purpose of this study was to investigate the specifics of performing classical violin repertoire on the prima mare using the example of Tchaikovsky's Violin Concerto in D major, Opus 35. The research methodology included a musicological analysis aimed at comparing the technical, timbre, and performance features of the two instruments and the influence of aesthetics and the way the instrument produced sound on the interpretation of a musical work. In addition, a survey was conducted among 60 professional performers, including 30 women and 30 men, at the Kurmangazy National Conservatory of Kazakhstan and the Kurmangazy State Orchestra of Kazakhstan. The study found that 40% of respondents considered the technical differences between playing the prima kobyz and the violin to be significant, and another 40% considered these difficulties to be moderate, indicating the need to adapt performance techniques. 50% of respondents noted the prima kobyz's high ability to convey lyrical timbre nuances, and 60% – its potential to create a new interpretive aesthetic in the performance of classical works. The analysis of the performance of the concerto on the prima kobyz showed that the unique timbre of this instrument contributed to the enrichment of the artistic and emotional content of the work and the expansion of its interpretive possibilities. The theoretical analysis revealed that the prima kobyz, as an instrument, along with the violin, had the potential to expand the performance repertoire by adapting classical works, such as Tchaikovsky's concerto.